On solutions of neumann boundary value problem for the liénard type equation - Atslega, Svetlana (Mathematical Modelling and Analysis, 2008)
We provide conditions on the functions f (x) and g(x), which ensure the existence of solutions to the Neumann boundary value problem for the equation x'' + f (x) x'2+g (x)=0.First Published Online: 14 Oct 2010